Impact of Crew Change on Contractual Adherence in Maritime Industry: A Case Study of PT. Amas Iscindo Utama - Mega Kurnia Putri; Larsen Barasa; Brenhard Mangatur Tampubolon (Dinasti International Journal of Education Management And Social Science, 2024)
This research investigates the repercussions of crew change practices on contractual adherence within the maritime industry, focusing on PT. Amas Iscindo Utama. Through a mixed-methods approach, quantitative data was collected via structured questionnaires and analyzed using SPSS, supplemented by qualitative insights derived from open-ended responses. Findings reveal that delayed crew recruitment significantly impacts contractual accuracy and compliance, leading to operational disruptions and challenges in crew management. Recruitment challenges, contractual inconsistencies, operational disruptions, and professionalism and standards emerged as key themes, underscoring the multifaceted nature of crew management dynamics. Strategic recommendations include streamlining recruitment processes, developing standardized contractual templates, fostering transparent communication channels, prioritizing professional development initiatives, and safeguarding crew welfare and rights. Collaboration among industry stakeholders is essential to implement proactive measures and uphold professionalism and adherence to contractual obligations within the maritime sector. This research contributes to advancing knowledge and best practices in crew management and contractual governance, informing policy decisions and interventions to enhance the sustainability and competitiveness of the maritime industry.